2014
DOI: 10.1177/0892705714530747
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and mechanical properties of polypropylene/calcium carbonate nanocomposites prepared from masterbatch

Abstract: Polypropylene (PP)/calcium carbonate (CaCO 3 ) nanocomposites were prepared from masterbatch by melt blending in a twin-screw extruder. The effect of three different nano-CaCO 3 loadings (5, 10, and 15 wt%) on the rheological/viscoelastic and mechanical properties of the nanocomposites was investigated. A scanning electron microscopy was used to study the morphology of the nanocomposites, whereas a differential scanning calorimetry was used to analyze the thermal properties. The rheological properties were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…It was known that toughness was more sensitive to the strain compared to the modulus elasticity. Additionally, the modulus elasticity, E for the PP/nano-CaCO3 composites also increased with the increase of nano-CaCO3 particles [37]. The enhancement of E was approximately 6.9, 12.7, and 16.6% with the addition of 5, 10, and 15 wt% of nano-CaCO3, respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…It was known that toughness was more sensitive to the strain compared to the modulus elasticity. Additionally, the modulus elasticity, E for the PP/nano-CaCO3 composites also increased with the increase of nano-CaCO3 particles [37]. The enhancement of E was approximately 6.9, 12.7, and 16.6% with the addition of 5, 10, and 15 wt% of nano-CaCO3, respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 85%
“…Whereas, for PP/CaCO3 nanocomposites, Chafidz, et al [37] reported that the Tc of the nanocomposites has also increased from 112°C to 117°C, which indicated that nano-CaCO3 also acting as nucleating agent, which enhanced the crystallization process, in which the crystallization process started earlier. The Xc value of the nanocomposites also slightly increased, which achieved maximum at 10 wt% of nano-CaCO3 loading (i.e.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…In general, the UFC-filled HDPE composites exhibited higher viscosities than the neat HDPE at lower shear rates (< 0.1 1/s). Chafidz et al (2014) discovered a similar phenomenon that was attributed to the restriction of molecular mobility and the reduction in free volume induced by the interaction and dispersion of cellulose in the polypropylene matrix. Similar to the storage modulus, the samples prepared using the SP compounding method (Fig.…”
Section: Rheological Propertiesmentioning
confidence: 92%
“…The melting temperature, Tm was taken as the highest/peak temperature of the DSC melting endotherm [30]. The crystallinity index of the composites can be determined from the heat of fusion (ΔHm) of DSC analysis and value of 100% of crystalline polymer material taken from the literature (ΔHm°) [31]. In which, the ΔHm° of the HDPE is approximately 292.6 J/g.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The decreasing crystallinity index by the addition of DPF was likely due to the restricted movement of the HDPE molecular chains by the presence of the, which also reduced the spaces/free volume available to be occupied by the molecular chains. Thus inhibiting the crystal growth and alignment of the crystal lattice, which consequently reduced the crystallinity index [31,33]. Figure 7.…”
Section: Thermal Propertiesmentioning
confidence: 99%